TINJAUAN TERHADAP BATAS MINIMAL USIA NIKAH DALAM UU NO.1/1974 DENGAN MULTIPRESPEKTIF - Salmah Fa'atin (YUDISIA : Jurnal Pemikiran Hukum dan Hukum Islam, 2015)
A review of the provisions of the minimum age limit for marriage contained in Article 7 paragraph 1 of Act 1 of 1974 is important, given the Qur’an as a source of law does not provide clear information in this regard. Almost all jurists’ four schools allows marriage under the age standard set forth in the provisions of Article 7 paragraph 1 of Law No. 1 of 1974, even Syafi’iyah schools, the majority of schools in Indonesia, allowing the marriage of women at the age of 9 years. While the minimum age to marry provisions contained in the Act, in the perspective of psychology including adolescent age category immature physically and psychologically. While the minimum age to marry provisions contained in the Act, in the perspective of psychology including adolescent age category immature physically and psychologically. Therefore a systematic study on the issue carried out by multi-perspective, the context of the concept of jurisprudence, law material itself and psychological approaches.